Implementasi Pencegahan Pernikahan Dini Menurut Peraturan Daerah NTB Nomor 5 Tahun 2021 Di Kabupaten Bima - Junaidin Junaidin; Lalu Hadi Adha; Allan Mustafa Umami (Fakultas Hukum Universitas Mataram, 2023)
The purpose of the research is to find out the NTB Regional Regulation Number 5 of 2011 implementation in society, especially regarding minor marriage in the Bima Regency. This study uses the empirical legal research method. The approach method uses the statute approach, the conceptual approach, and the sociological approach. However, the factors that affected minor marriage consist of: parents, promiscuity, customs, education, and economy. The result of this study showed the implementation of NTB Regional Regulation Number 5 of 2021 in the prevention of minor marriage in Bima Regency and the factor that affected minor marriage prevention in Bima Regency. The local government and KUA work together with the district government and village government, they socialized the negative effect of minor marriage.